Curriculum as unquestioned hegemony: Trends that reveal the exclusion of Ethiopian primary school curriculum content from researchers’ critical look - Meskerem Lechissa Debele (Bahir Dar Journal of Education)
Curriculum is the most central component of the broad package we call “education”. Hence, the relevance and substance of the curricula offered in different academic subjects is naturally assumed to be the major focus of educational research. However, a glance at most studies on Ethiopian primary education indicates a serious neglect of curriculum content as the main focus of educational research. This paper is a review of 74 research studies available online and conducted between 1995 and 2015 on Ethiopian primary education and school children in order to understand what issues are often studied about primary education in Ethiopia, and to what extent curriculum content is given attention by researchers. The examination of the main focus of each study revealed that curriculum content is dealt with only by seven studies, among which, only three studied it directly. Possible reasons for this exclusion of primary school curriculum content from the focus of educational research and the way forward are discussed